Impact of Fiber Buildup Stacking Sequence on Thermo-Mechanical Behaviour of Natural Fiber–Reinforced Anamide Composites - M. Subramanian; M. Diviya; S. Kaliappan; A. Deepak; Kuldeep K. Saxena; Nasim Hasan (International Journal of Polymer Science)
This article focuses on the viscoelastic behaviour of the anamide composites using a dynamic mechanical study developed by hot compression moulding technology at higher temperatures. The frequency range for this analysis is 1 Hz. In the nitrogen atmosphere, thermogravimetry analysis differential scanning calorimetry was used to investigate the thermal stability of composite laminates with various fiber orientations. The findings showed that a glass transition temperature close to 100°C can be achieved at 1 Hz to increase the fiber orientation of the basalt fiber-enhanced anamide compounds. Through the thermo-gravimetric analysis experiments, the excellent thermal stability of composite laminates at temperatures above 600°C was conspicuous. Analysis using the Fourier transform infrared (FTIR) spectroscopy envisioned the surface chemical properties of anamide films at various fiber orientations, and the interaction properties between fiber and matrix were determined. Scanning electron microscopy on composite laminate surfaces proclaimed that the interface relationship between the basalt fiber and the anamide material is superior with FTIR findings being assisted. The findings demonstrate that composite laminates may be a good replacement for high-performance and high-temperature applications since they are thermally extremely robust with great rigidity.